Habitat Preferences and Environmental Characteristics of Coconut Crab (Birgus Latro) On Hiri Island, Ternate City - Abubakar, Yuyun; Sunarti, Sunarti; Salim, Fajria Dewi (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
The coconut crab is a marine biota that spends most of its adult phase in the terrestrial environment. Coconut crabs are also economically valuable because they can be traded as food ingredients and body frames used as home jewelry. However, the coconut crab is classified as a rare animal, and the distribution area is getting narrower. The purpose of the study was to determine habitat preferences and environmental characteristics. The research was carried out in the Tomajiko sub-district, Hiri Island district. Implementation time for six months from April – September 2021. Data Collection Procedure. The determination of the station is determined based on the difference in location or distance from the residential area. Sampling stations were determined at 3 (three) coconut crab fishing locations, namely stations I, II, and III with stations. The study results obtained 53 individuals who were female, 25 canary crabs, and 28 males, with a sex ratio obtained. During the study 1:1, there was a balance. Among the three stations, coconut crabs were mainly found in Station I, which had soil temperature, soil pH, and relative humidity suitable for the life of coconut crabs compared to other stations.